Clinico-bacteriological profile of neonatal septicemia in a tertiary care hospital - Shipra Galhotra; Veenu Gupta; Harmesh Singh Bains; Deepinder Chhina (Journal of Mahatma Gandhi Institute of Medical Sciences, 2015)
Introduction: Neonatal septicemia is a major cause of mortality and morbidity. Surviving neonates can have significant neurologic sequelae, septic shock or hypoxemia. The spectrum of bacteria that cause neonatal septicemia varies in different parts of the world. The management of these infections is being complicated by the emergence of antibiotic resistance. The aim of this study was to determine the etiology, clinical characteristics and outcome of neonatal septicemia cases. Materials and Methods: During a 1-year study, 257 clinically suspected cases of neonatal sepsis were enrolled and classified as early onset septicemia (EOS) and late onset septicemia (LOS) based on appearance of signs and symptoms, i.e. within or after 72 h, respectively. Blood culture was performed using BACTEC 9240, isolates were identified by standard techniques and antibiotic susceptibility was performed as per the CLSI guidelines. Risk factors associated with neonatal sepsis were recorded and analyzed with respect to culture-proven sepsis. Results: In both suspected and culture-proven sepsis cases, majority of the neonates were male, pre-term and low birth weight babies. The prevalence of EOS and LOS was 82.4% and 17.5%, respectively. Culture positivity was seen in 7.8% of the cases. In culture-proven septicemia, 55% neonates presented with EOS and 45% presented with LOS. Gram positive isolates were more as compared with Gram negative isolates. The most common isolates were S. aureus, S. epidermidis and E. coli. All Gram positive isolates were sensitive to vancomycin and linezolid, while carbapenems and polymyxin B were the most effective drugs in the Gram negative isolates. Mortality was higher in LOS as compared with EOS cases, and the difference was statistically significant. Conclusion: Gram positive pathogens were predominant in septicemia. Vancomycin and linezolid were the most effective antibiotics for Gram positive isolates and carbapenems for most effective Gram negative organisms.